Significance of weakly positive urine pregnancy tests - Suguna R. Kumar; Vidya A. Thobbi; Sureka A. Nayak (Al Ameen Medical College, 2013)
Objective: The objective of this study was to determine the pregnancy outcome of weakly positive urine pregnancy tests in 207 women by transvaginal sonograghy (TVS). Background: Urine pregnancy test (UPT) also called Home pregnancy test (HPT) currently make up the fastest growing segment of home diagnostic testing market. These tests give a significant results as a weakly positive pregnancy test (hCG 25-50IU/L) and a positive pregnancy test (hCG >50IU/L), but both the results are reported as a positive pregnancy test by a non- professional. Human gonadotropin (hCG) levels indicate the health of the trophoblastic tissue, low level of βhCG is associated with poor decidual reaction. A weakly positive result indicates low hCG level and requires further evaluation. Method: Women visiting Antenatal Clinic for confirmation of pregnancy with weakly positive UPT were advised repeat UPT after 48hours on morning urine sample, repeat UPT with weakly positive results were advised TVS to known the pregnancy outcome. Result: TVS of these weakly positive results showed early pregnancy failure (EPF) in 138(66.6%), viable pregnancy 58 (28%) and no pregnancy in 11(5.3%). Conclusion: Thus these kits require a manufactures instruction to distinguish positive and weakly positive results and an advice for further evaluation by an expert to known the pregnancy outcome and to prevent the complications of interference in non- pregnant status and continuation of EPF